"The Jesuits and globalization: historical legacies and contemporary challenges" - Romero Rodríguez, José Juan (Revista de Fomento Social, 2018)
Reseña de la obra de: BANCHOFF, T. y CASANOVA, J. (Eds.) (2016), The Jesuits and globalization: historical legacies and contemporary challenges. Washington D.C., Georgetown University Press, 299 pp.